ACHIEVEMENT THE GOALS OF EXPANSION AND PREVENTION COMBINATION TOWARD HIV DISEASE AMONG ADOLESCENTS IN JEMBER - Gilang Ramadhan; Ahmad Rifai; Dicky Endrian Kurniawan (Jurnal Keperawatan Malang, 2022)
Background: The second leading cause of death in children and adolescents worldwide is HIV and AIDS. The Indonesian government has implemented the 2015-2019 HIV and AIDS National Strategy and Action Plan (SRAN). One of the program objectives is the expansion and improvement of combination HIV prevention. High knowledge and low-risk behavior are one of the targets of HIV prevention in adolescents. Aims: This study was aimed to analyze the implementation of the 2015-2019 SRAN, knowledge of HIV / AIDS, and risk behavior among adolescents in Jember. Method: The research design used quantitative descriptive. A total of 100 adolescents aged 17-22 years in rural areas were involved using the purposive sampling technique. Data on SRAN implementation, HIV / AIDS knowledge, and risk behavior were collected using a close-ended questionnaire. Results: The implementation of SRAN among adolescents still low (81%), although most of the adolescents' knowledge of HIV / AIDS was high (85%), and most adolescents had no risk behavior (85%). The low implementation of the SRAN is because adolescents do not yet know about the HIV and AIDS prevention policies. Conclusion: Nurses as educators can provide deeper outreach to adolescents about HIV and AIDS prevention policies. The need to comprehensively analyze the implementation of SRAN apart from adolescents' knowledge and behavior toward achieving HIV prevention targets. Keywords: Knowledge of HIV / AIDS, Risk Behavior; Youth; HIV prevention.